Analysis of Implementation of Cooperative Accounting Based on PSAK No. 27 In The Financial Reports of Employees Cooperative PT. Cement Tonasa Pangkep District - Elvira Fajrianti (JEKAMI Journal of Accounting, 2022)
This study aims to determine whether the application of cooperative accounting financial statements of employees of PT. Semen Tonasa Pangkep Regency is in accordance with PSAK No. 27. This type of reseach with a qualitative descriptive appoarch to processed data source that are primary data source and secondary data. The results of this study, PT Semen Tonasa Pangkep Regency bel completely in accordance with PSAK No. 27 because in the presentation there is no report on the economic promotion of members, the balance sheet at PT. Semen Tonasa Pangkep’s employee cooperative is presented comparatively with the previous year and in accordance with PSAK No. 27, the cash flow statement of PT. Semen Tonasa co-perative employees in pangkep district is presented in a comperative manner by presenting operating activities, investment activities, funding activities, the report on the calculation of the remaning results of operations (RRO) is presented directly, but the estimated cost of goods is presented separately outside the expense group. The notes to the financial statements describe the policies taken and so on that are deemed necessary tobe disclosed in the notes to the financial statements. The report on the calculation of the remaining results of operations is presented directly, but the estimated cost of goods is presented separately outside the expense group. The notes on the financial statements explain the policies taken and so on that are deemed necessary to be disclosed in the notes to the financial statements.